2004
DOI: 10.1242/dev.01022
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental failure of substantia nigra dopamine neurons in mice lacking the homeodomain genePitx3

Abstract: The mesencephalic dopamine (mesDA) system is involved in the control of movement and behavior. The expression of Pitx3 in the brain is restricted to the mesDA system and the gene is induced relatively late, at E11.5, a time when tyrosine hydroxylase (Th) gene expression is initiated. We show here that, in the Pitx3-deficient aphakia(ak) mouse mutant, the mesDA system is malformed. Owing to the developmental failure of mesDA neurons in the lateral field of the midbrain,mesDA neurons are not found in the SNc and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
313
3
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(339 citation statements)
references
References 48 publications
17
313
3
6
Order By: Relevance
“…Additionally, it is unclear how the striatal transcriptome responds to persistent dopaminergic denervation over time. Studies have reported increased, decreased or unchanged mRNA expression levels of dopamine receptors and neuropeptides in ak mice (Smidt et al, 2004;Smits et al, 2005;van den Munckhof et al, 2006). These inconsistencies may lie in differing methodologies used to assess striatal expression of these proteins or their transcripts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it is unclear how the striatal transcriptome responds to persistent dopaminergic denervation over time. Studies have reported increased, decreased or unchanged mRNA expression levels of dopamine receptors and neuropeptides in ak mice (Smidt et al, 2004;Smits et al, 2005;van den Munckhof et al, 2006). These inconsistencies may lie in differing methodologies used to assess striatal expression of these proteins or their transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…The Pitx3 −/− or aphakia (ak) mouse is a promising model of striatal denervation in PD as it exhibits the cell specificity of neurodegeneration observed in humans (Hwang et al, 2003;Nunes et al, 2003;Smidt et al, 2004), similar neuroadaptive phenomena at the level of the striatum (Smits et al, 2005;van den Munckhof et al, 2006), and locomotor deficits that are rescued by levodopa van den Munckhof et al, 2006). Pitx3 is a member of the pituitary family of bicoid type homeobox transcription factors (Semina et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression analyses and loss-of-function knockout mouse studies have revealed roles for additional transcription factors in the specification and maturation of midbrain DA neurons, including the homeodomain proteins Lmx1b (5), Pitx3 (6)(7)(8)(9), and En1 (10,11). None of these factors are uniquely expressed in midbrain DA neurons, nor are they required for TH expression.…”
mentioning
confidence: 99%